Cyclooxygenase Inhibitors as a New Therapeutic Strategy in Small Bowel Transplantation. Issue 11 (November 2016) - Schildberg, Frank Alexander; Liu, Bin; Afify, Mamdouh; Steitz, Julia; Paschenda, Pascal; Schäfer, Nico; Kalff, Jörg C.; Minor, Thomas; Tolba, René Hany
Abstract : Background: The long-term outcome of intestinal transplantations is still not favorable, which is partly due to the intestinal susceptibility to ischemia. There are several indications that the inflammatory response to ischemia-reperfusion injury is mediated by cyclooxygenases and that their inhibition may be associated with improved organ function. The aim of this study was to analyze if cyclooxygenase (COX) inhibitors could improve the early posttransplant outcome after orthotopic small bowel transplantation. Methods: Small bowel transplantation was performed between rats to test the impact of nonselective (Piroxicam), preferential (Meloxicam), and selective COX-2 inhibitors (Parecoxib). The donor intestines were either perfused and stored with inhibitor or had inhibitor administered intravenously after transplantation. Results: Using COX inhibitors, a sequential increase of posttransplantation intestinal integrity could be shown, with Parecoxib the least effective and Meloxicam the most effective treatment. These differences were in line with the downregulation of COX-2 activity by the inhibitors. Functionally, the same tendency could be seen in diminished expression of proinflammatory molecules, decreased leucocyte inflammation, and significantly improved graft microcirculation. In most cases, the intravenous administration was more effective. However, the COX inhibitors used were shown to cause relevant hepatotoxicity under nearly all conditions, but particularly under intravenous administration. Only Meloxicam in histidine-tryptophan-ketoglutarate was demonstrated to be a safe drug without hepatotoxic side effects. Conclusions: The activity of COX contributes to ischemia-reperfusion injury after intestinal transplantation. In this comparative study, the administration of the preferential COX-2 inhibitor Meloxicam via histidine-tryptophan-ketoglutarate showed the best graft-protective attributes and the lowest hepatotoxic side effects. Abstract : Schildberg et al compare the ability of 3 COX inhibitors to alleviate posttransplant intestinal tissue damage induced by ischemia reperfusion injury and show that the preferential COX-2 inhibitor Meloxicam has the best graft-protective attributes with the lowest hepatotoxic side effects.